Endotoxin-induced acute lung injury in mice with postnatal deletion of nephronectin. - Carole L Wilson; Chi F Hung; Lynn M Schnapp (PLoS ONE, 2022)
Acute injury of the lung involves damage to the epithelium and its underlying extracellular matrix (ECM), the basement membrane (BM). How BMs contribute to injury resolution is poorly understood. Nephronectin (NPNT) is a high-affinity ligand for integrin α8β1 and, although first identified in the mouse kidney, is prominently expressed in the lung, where it localizes to BMs in the alveoli. To determine if NPNT plays a role in acute injury and inflammation of the lung, we developed a model for postnatal deletion of NPNT using mice with a floxed allele of Npnt in combination with a tamoxifen-inducible Cre recombinase expressed at the ROSA locus. Expression of NPNT was substantially reduced in lungs from tamoxifen-treated Cre+ animals. Cre+ mice and Cre- controls were given E. coli LPS by oropharyngeal aspiration to induce injury and inflammation. In Cre- lungs, although both Npnt and Itga8 (integrin α8) transcripts were downregulated at the peak of inflammation, NPNT protein was still detectable. While the onset of inflammation was similar for Cre+ and Cre-, NPNT-deficient lungs still had thickened alveolar septa and there were increased macrophages in the bronchoalveolar lavage fluid (BALF) in the resolution phase. BALF from Cre+ lungs was more chemotactic for bone marrow-derived macrophages than Cre- in in vitro experiments, but there were no differences in the elaboration of chemokines in vivo. We speculate that absence of NPNT in BMs of the alveoli impairs or delays inflammatory and injury resolution in this model, but further studies are needed to establish the precise role of NPNT in tissue repair.